The Effect of Garlic Extract on Reducing Blood Pressure in Hypertension Patients - Asnuddin; Muhammad Tahir; Sahariah (Journal Of Nursing Practice, 2023)
Background: Hypertension is a condition that is often found in primary health care. Basic Health Research data for 2018 show that the prevalence of hypertension in Indonesia is 34.1%. Efforts that have been made to reduce the impact of hypertension include pharmacological and non-pharmacological therapies. Herbal therapy is included in complementary therapy, one of the herbal therapies to reduce blood pressure is the consumption of garlic. Garlic contains allicin and hydrogen sulfide which dilate and make blood vessels less rigid so blood pressure will decrease. Purpose: To determine the effect of garlic extract on reducing blood pressure in hypertensive patients. Methods: This is a pretest-posttest pre-experimental study for the causal relationship of garlic extract with a decrease in blood pressure. The samples of this study were hypertensive patients. The statistical tests used were the friedman test to compare pre, post-1, and post-2 and the Wilcoxon test to compare two repeated observations which were analyzed using Software Program Statistics System.  Results: For systolic blood pressure, the statistical test results obtain a p-value of (0.000) <0.05, which means that there is a change in blood pressure between pre, post-1, and post-2, with a change in magnitude of 13.43. Meanwhile, for diastolic blood pressure, the statistical test results obtain a p-value of (0.000) <0.05, which means that there is a change in blood pressure between pre, post-1, and post-2, with a change in magnitude of 8.67. Conclusion: There is an effect of garlic extract on reducing blood pressure in hypertensive patients.